2023
DOI: 10.1002/adma.202211840
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh‐Flux X‐ray Detection by a Solution‐Grown Perovskite CsPbBr3 Single‐Crystal Semiconductor Detector

Abstract: Solution-processed perovskites are promising for hard X-ray and gamma-ray detection, but there are limited reports on their performance under extremely intense X-rays. Here, a solution-grown all-inorganic perovskite CsPbBr 3 single-crystal semiconductor detector capable of operating at ultrahigh X-ray flux of 10 10 photons s −1 mm −2 is reported. High-quality solution-grown CsPbBr 3 single crystals are fabricated into detectors with a Schottky diode structure of eutectic gallium indium/CsPbBr 3 /Au. A high rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Over the past few years, three-dimensional (3D) halide perovskites have attracted intensive attention for X-ray detection, owing to their excellent absorption coefficients, high carrier mobility, long carrier diffusion length, high defect tolerance, and tunable band gaps. For example, Tang et al provided X-ray detectors based on intrinsic CsPbBr 3 , which achieved a low detection limit of 103.6 nGy air s –1 . Kanatzidis et al reported CsPbBr 3 -based X-ray detectors with a low detection limit of 22 nGy air s –1 . Besides, MAPbI 3 has also been used for X-ray detection with a detection limit of 340 nGy air s –1 .…”
mentioning
confidence: 99%
“…Over the past few years, three-dimensional (3D) halide perovskites have attracted intensive attention for X-ray detection, owing to their excellent absorption coefficients, high carrier mobility, long carrier diffusion length, high defect tolerance, and tunable band gaps. For example, Tang et al provided X-ray detectors based on intrinsic CsPbBr 3 , which achieved a low detection limit of 103.6 nGy air s –1 . Kanatzidis et al reported CsPbBr 3 -based X-ray detectors with a low detection limit of 22 nGy air s –1 . Besides, MAPbI 3 has also been used for X-ray detection with a detection limit of 340 nGy air s –1 .…”
mentioning
confidence: 99%
“…Due to the outstanding bias stability, an excellent sensitivity of 7.3 × 10 4 μC Gy air s −1 cm −2 is achieved for the Au/Al/BCP/C 60 / CsPbBr 3 /Au device at 100 V (Figure 5d), which is one of the highest sensitivities achieved by detectors based on CsPbBr 3 SCs. 48,49 The corresponding on−off responses to fit the sensitivity curves are shown in Figure S7. However, for Au/Al/ CsPbBr 3 /Au, the sensitivity is limited for the instability caused by a severe electrochemical reaction (Figures S8 and S9).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…3 A high sensitivity and a low detection limit are two important parameters for X-ray detectors to acquire a high image resolution while minimizing damage to the human body. 11 The highest reported sensitivity of 2.2 ×10 8 µC Gy air −1 cm − 2 for 8 keV X-ray photons has been achieved in MAPbI 3 lms, which is 6-7 orders of magnitude larger than that for α-Se (20 µC Gy air −1 cm − 2 ). 12 Generally, such high sensitivities were attained with several hundred micrometre perovskite lms in the detection of soft X-rays below 50 keV with a strong photoconductive gain effect in the thin lms.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, low trap concentrations are essential for SC X-ray detectors to obtain a high CCE, which provides high sensitivity while maintaining a low detection limit. 11 Among all perovskites, the all-inorganic halide perovskite CsPbBr 3 SC has attracted considerable attention for its great structural and thermal stability compared to organic-inorganic hybrid perovskites.…”
Section: Introductionmentioning
confidence: 99%